Phase field approach based brittle fracture study for a single edge centre-notched specimen under plane stress/strain condition - Khandelwal, N.; Murthy, A. Ramachandra (Journal of Structural Engineering, 2024)
In the last few years, the application of variational approach-based phase field model in fracture mechanics has gainedattention for simulating complicated crack behavior. The phase field model does not require the presence of predefinedcracks. Crack path in the phase field model for damaged material is tracked by a phase field variable that variesbetween 0 and 1. This paper aims to carry out fracture analysis of quasi-static brittle specimen under plane stress andplane strain conditions using phase field method. Phase field modelling for two-dimensional quasistatic brittle fracturehas been implemented using user-defined subroutines in ABAQUS software. Centre-notched specimen under mode-Iand mode-II loading were analysed and the predicted behaviour compared with the literature. The effect of thicknesson load carrying capacity of specimens were investigated and it was observed that for similar thickness, load carryingcapacity is higher and occurance of fracture delayed in plane stress condition as compare to plane strain case. Otherobservations from the study include that thickness does not have any effect on the displacement at which suddenfracture occur, in both plane stress and plane strain cases.